Rituximab in the treatment of Graves’ disease and endocrine ophthalmopathy. Opportunities and limitations - T. S. Panevin; E. G. Zotkin; E. A. Troshina; G. V. Lukina (Научно-практическая ревматология, 2023)
Rituximab is a chimeric (mouse and human) monoclonal antibody against B-lymphocytes (CD20). This drug is widely used in rheumatology in the treatment of rheumatoid arthritis, Sjogren’s syndrome, some systemic connective tissue diseases and vasculitis, as well as in hematology in lymphoproliferative diseases. Administration of rituximab leads to depletion of B-lymphocytes through various mechanisms, including antibody-dependent and complementdependent cytotoxic effects, as well as the regulation of apoptosis. Considering the mechanism of autoimmune damage in Graves’ disease, an autoimmune thyroid disease accompanied by thyrotoxicosis and endocrine ophthalmopathy (an autoimmune lesion of the accessory apparatus of the eye), the use of rituximab may be effective in these diseases. The review considers the currently available results of studies on the use of various doses of rituximab in these diseases.